GAGASAN OPTIMALISASI KONSEP OTONOMI DAERAH SELUAS- LUASNYA DI NEGARA KESATUAN REPUBLIK INDONESIA - M. Ar Huzaifi Samani; Mexsasai Indra; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the implementation of regional autonomy that uses the principle of decentralization,in fact it does not apply optimally. For example, the state budget provided by the centralgovernment with the aim of increasing the level of economy and welfare for the people ineach region. This is based on the provisions of Law 33 of 2004 concerning FinancialBalance between the Central Government and Regional Governments. Where in this caseit is stated that the regional government is obliged to deposit regional wealth that has beenobtained to the central government even from the results of natural wealth owned by thearea. Especially in the reality on the ground that the independence of each region to getthe word prosperous is very far from what was expected.It is the unclear format of regional autonomy that makes the central governmentimplement an excessive centralized system (overcentralization). Excessive centralizationhas destroyed the government system created by the New Order, the destruction of the NewOrder government through the reform movement has confirmed the intention of theIndonesian people to create a just and prosperous nation. Regional natural resources areexploited by the center and given unfairly and not transparently, regional privileges areundervalued and even generalized by the Central Government. The reform movement,which brought fresh air of democracy, has inspired some people to create an Indonesianstate structure within the framework of Federalism, this is in view of the emergence of thethreat of disintegration that has occurred as a result of the centralized system of unitarystate government and the many demands of regional governments for independence, suchas Papua, and others.This research will examine the main issues according to the scope and identificationof problems through a normative juridical approach. Based on normative researchmethods, the data sources used in this study are secondary data sources which consist of 3legal materials, namely: primary legal materials, secondary legal materials, and tertiarylegal materials. Data collected from literature studies.Keywords: The Idea of Optimization - Concept - Regional Autonomy - As Wide asPossible - The Unitary State of the Republic of Indonesia